PENGEMBANGAN INKUBATOR KEWIRAUSAHAAN DI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Suranto Suranto; Muhtadi Muhtadi; Kuswaji Dwi Priyono; Totok Budi Santosa (Universitas Muhammadiyah Surakarta, 2016)
Business Entrepreneurial Incubator Program (Inwabi) programmed for entrepreneurship aims to implement the role of science and technology for entrepreneurship for students at the University of Muhammadiyah Surakarta (UMS). Activities include: recognition, empowerment, improvement of hard and soft skills of students, mental construct of student entrepreneurship (entrepreneur soft skills), so that students are able to be creators of jobs (job creators) not only job seekers (job seekers). The target of the program Inwabi provide assistance to the 20 students in the field of new entrepreneurial small businesses and make at least 50% managed to independently manage their own businesses. Methods of community service Papiku in Inwabi include learning, training and empowerment using the concept of Project Based Learning (PBL), which contains models of mentoring, empowerment: doing, empowering, facilitating and evaluating. Besides PBL also uses Participatory Rural Appraisal (PRA) of potential exploration-based talent to produce and acquire prospective new entrepreneurs accordance talent / potential of each. Implementation conducted on students who are ready to become tenants, including students PKMK, students starting a new business that already have a business. Inwabi Papiku activities include direct entrepreneurial training and learning (doing), empowered (empowering), facilitated by (facilitating), and evaluated the problem constraints (evaluating) for three months. Implementation of assistance Papiku Inwabi carried out cooperation and synergy with the institutions Socialpreneur who have competence in their fields, namely (a) the Vocational School, supports hardware-based technology, training, learning and training, (b) Talents Center, to support the implementation of potential exploration entrepreneur based talent / potential, (c) Kemal Abda, an online shop is a community in the field of internet marketing. Tenant business group in Inwabi activities covering the fields of internet marketing online shop (11), the culinary field (3), in batik and fashion (2), the culinary field (4), the implementation is divided into seven stages. During the three months generated at least 50% independent of the number of 20 tenants, 10 students (tenant) became new entrepreneurs are well established, the rest is still to understand the importance of entrepreneurship and self-employment as a mental construct a selection of work for him to be more independent.